2010
DOI: 10.5301/hip.2010.858
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results after anterior mini-open approach for femoroacetabular impingement in early degenerative stage

Abstract: We describe our modified anterior mini-invasive technique and results obtained in our first consecutive 117 cases in 105 patients. To assess the influence of preoperative Tönnis degenerative stage, cases were divided into group A (Tönnis 0, 32 hips), B (Tönnis 1, 61 hips), and C (Tönnis 2, 24 hips). The clinical score Dexeus combined score (DCS) was used preoperatively, 3 months, 6 months, and every year after operation. At 3-month follow-up, impingement test results improved significantly in 30 hips of group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…Pain and functional outcomes were measured using various standardized scoring methods. Of the seven studies measuring pain and functional scores, four used the Harris Hip Score 21 (HHS) two used the Western Ontario and McMaster Universities (WOMAC) arthritis index 3 and one used the Merle d'Aubigné-Postel 8 and the Dexus combined score 29 . All included studies noted whether a repeat arthroscopy or hip arthroplasty was offered or performed for any patient.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pain and functional outcomes were measured using various standardized scoring methods. Of the seven studies measuring pain and functional scores, four used the Harris Hip Score 21 (HHS) two used the Western Ontario and McMaster Universities (WOMAC) arthritis index 3 and one used the Merle d'Aubigné-Postel 8 and the Dexus combined score 29 . All included studies noted whether a repeat arthroscopy or hip arthroplasty was offered or performed for any patient.…”
Section: Resultsmentioning
confidence: 99%
“…The same study noted that patients with Tonnis grade 0 and 1 had significant improvement in clinical outcome scores (P < 0.001) at 1 year and remained unchanged at subsequent yearly follow-ups. 29 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…43,44 However, it has been demonstrated that the vast majority of chondral and labral lesions are located in the accessible area of this surgical approach. 45 One of the strategies that can be used to improve the view of the central compartment during a mini-open approach is to use of a 70° arthroscope, which allows a thorough evaluation of the central compartment of the hip 46,47 ; however, we did not use this technique. We also accept that the use of other methods to classify articular cartilage and labral pathology [48][49][50][51] could have led to a different result with regard to the predictive value of the studied variables.…”
Section: Discussionmentioning
confidence: 99%